PENEMPATAN KERJA, KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA PEGAWAI SEKRETARIAT DPRD LOMBOK TIMUR - Aida, Yusron; Mulyono, Sugeng; Gunadi, Gunadi; Sulaiman, Sulaiman (Universitas Hamzanwadi, 2023)
The aim of this research is to prove and analyze the influence of job placement and job characteristics on job satisfaction of East Lombok Regency DPRD Secretariat employees. The type of research used is explanatory research. The analysis technique is carried out using multiple linear regression. The results of this research are that partially, work placement and job characteristics have a significant effect on job satisfaction of East Lombok Regency DPRD Secretariat employees. Likewise, simultaneously, work placement and job characteristics influence the job satisfaction of East Lombok Regency DPRD Secretariat employees with an influence contribution of 41.2%.